HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN SOCIAL LOAFING PADA MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS WIJAYA PUTRA SURABAYA - Anggoro, Husni; Lusiani, Nofita; Ula, Ilma Iftahul; Irmayanti, Nur (Esa Unggul University, 2022)
The purpose of this study was to see how the relationship between self-confidence and social loafing in Psychology Faculty students, Wijaya Putra University, Surabaya. Self-confidence is defined as a student's belief that he or she is able to develop their abilities to obtain the expected results and is not easily influenced by others. Meanwhile, Social Loafing is the tendency of students to expend less effort in achieving goals when in a group than if they achieve the goals themselves. This study uses a quantitative method of Pearson bivariate correlation analysis with the help of the SPSS program. The scale used is the self-confidence and social loafing scale adapted from research conducted by (Munawwaro, 2020). The subjects in this study were 55 students. The results of the Pearson bivariate correlation analysis obtained a value (r=-0.650; p<0.01). The results showed that there was a significant relationship between self-confidence and negative social loafing. This means that the higher the level of self-confidence, the lower the social loafing of students, and vice versa, the lower the level of self-confidence, the higher the social loafing of students